Quantitative convergence theorems for a class of Bernstein–Durrmeyer operators preserving linear functions - Gonska, H.; Peltenia, R. (Український математичний журнал, 2010)
We supplement recent results on a class of Bernstein–Durrmeyer operators preserving linear functions. This is done by discussing two limiting cases and proving quantitative Voronovskaya-type assertions involving the first-order and second-order moduli of smoothness. The results generalize and improve earlier statements for Bernstein and genuine Bernstein–Durrmeyer operators.